Haemodynamic indicators of arteriolar dysregulation during combined hyperventilation and exercise test in patients with ANOCA (SESPASM). (3rd October 2022) - Dedic, S; Boskovic, N; Giga, V; Nedeljkovic, I; Tesic, M; Jovanovic, I; Aleksandric, S; Beleslin, B; Ciampi, Q; Picano, E; Djordjevic Dikic, A
Abstract: Introduction: In patients with angina and non-obstructed coronary arteries (ANOCA), functional dysregulation such as epicardial coronary spasm and microvascular dysfunction (microvascular spasm and /or impaired microvascular dilatation) frequently coexist. The aim was to analyse haemodynamic indicators of arteriolar dysregulation during combined hyperventilation and exercise stress echo test in patients with ANOCA. Methods: In a prospective study we enrolled 38 patients (56±13 years, 31 females) with ANOCA, proven by normal coronary angiogram. Stress echocardiography protocol with Doppler measurements of coronary flow consisted of hyperventilation test for spasm provocation (HYP, respiratory rate of 30 per min for 5') followed by supine bicycle exercise test (HYP+EXE) for assessment of endothelium dependent function. Adenosine test was done (ADO 140 mcg/kg in 1 min) for estimation of endothelium independent vasodilatation. Coronary flow velocity (CFV) was assessed in distal LAD by Transthoracic Doppler echocardiography at the end of the each stage of the test. Abnormal response to HYP was a CFV ratio (stress/rest) <1.0 (vasoconstrictor response). CFV ratio at peak HYP+ EXE was an indicator of endothelial dependent vasodilatation (<2 blunted response). An abnormal response to ADO was a CFV reserve <2.0 (blunted vasodilatory response). Results: The double product increased during HYP in comparison to rest (13263 vs 10321, p<0.001), and further increased with EXE (23817 vs HYP, p<0.001). Chest pain was present in 6 pts during HYP, and in additional three pts during HYP+EXE (15.8% vs 23.7%, p=0.25). ST segment depression was present in 6 pts during HYP and 23 during HYP+EXE (15.79% vs 60.52%, p<0.001). Wall motion abnormality was provoked with HYP in three pts (7.89%) and in ten (26.3%) with HYP+EXE (p=0.016). CFV ratio was abnormal for vasoconstriction during HYP in 16 (42.1%) and blunted in 23 (60.52%) pts during HYP+EXE (Fig 1). Vasodilation during ADO was preserved in all patients, but one. There was significant difference between CFV reserve during HYP+EXE vs ADO (1.98±0.49 vs 2.53±0.43 respectively, p<0.001) (Fig. 2). Conclusion: Our results indicate that HYP induce microvascular dysfunction with vasospastic component which is reflected in reduced CFV ratio. This prevents the normal hyperemic response during EXE in more than a half of patients. Endothelial independent vasodilatation during ADO hyperemia was perserved in all patients, excluding structural microvasculature remodeling. HYP+EXE provocation with noninvasive measurement of coronary flow is a promising test for assessing mechanism of arteriolar dysregulation in ANOCA patients. Funding Acknowledgement: Type of funding sources: None.